Infections in gynecology and obstetrics. Postoperative infections. - Trelles Yenque, Juan (2015)
The post major surgery of gynecological patients infection is a serious problem for any service of obstetrics and gynecology, because it increases morbidity and mortality, prolonged hospital stay, increased use of antibiotics and demand greater attention by qualified personnel.